Aligning International Ranking Indicators with Institutional Review Standards in Sri Lankan Universities and the Role of Academic Librarians in Enhancing Research Excellence - Janen, T. (University Librarians Association of Sri Lanka, 2024)
The Quality Assurance Council (QAC) of the University Grants Commission of Sri Lanka assesses how well universities meet quality standards and respond to the needs of stakeholders in higher education. This process ensures that educational offerings align with national and international standards. At the same time, international ranking of Higher Education Institutions (HEIs) has attracted the attention of many stakeholders of HEIs. This paper examines the relationship between the research-related indicators of International Ranking Systems (IRS) and the research criteria used in the Institutional Review (IR) process followed by Sri Lankan universities. Based on this analysis, the study proposes strategies for academic librarians to contribute to enhancing research excellence within these institutions. The study focused on four major IRS namely, Times Higher Education (THE) World University Ranking, Quacquarelli Symonds Ranking (QS), University Ranking by Academic Performance (URAP), and SCImago Institutional Ranking. Ranking methodology, indicators, and data sources were obtained from the official websites of the ranking systems. Quality Assurance Institutional review manual (2023) and IR scoring sheet (2019), were analyzed and compared with the research performance criteria and methodologies of these ranking systems. Detailed mapping revealed that, 82.5% of THE research indicators matched with IR standards, QS matched 50%, URAP matched 100% and SCImago matched 50%. Concluding that IR includes the research related indicators expected by IRS. While international rankings and the IR process have different focuses and methodologies, both aim to enhance the quality and performance of higher education. Sri Lankan universities can improve their research performance and align with IRS by following IR criteria related to Postgraduate studies, research innovation and commercialization. In this process, academic librarians can contribute to enhance their institutions' research performance through various roles. They can embed themselves in research projects, collaborate with faculty and provide specialized support services - such as information literacy programs, access to high-quality databases, collection development, conduct bibliometric and citation analyses, support open access publishing, and oversee institutional and research repositories. These activities ensure that researchers have the tools and resources needed to improve research visibility and performance.
Keywords: Quality Assurance Council; International ranking systems; Institutional review; Research performance indicators